Presidential Discretion and Ministerial Inflation: A Normative Critique of the Amendment to Indonesia’s State Ministry Law - Akbar, Muhammad Jihadil; Uyun, Dhia Al; Prasetyo, Ngesti Dwi (Invest Journal of Sharia & Economic Law, 2025)
The amendment to Article 15 of the State Ministry Law, which eliminated the cap on ministries and replaced it with "as needed by the President," has introduced legal uncertainty in Indonesia. This change adversely affected the structuring and formation of state ministries. This study analyzes the factors influencing ministry formation and aims to reconstruct the regulatory framework by reinstating limitations on the number of ministries to mitigate negative impacts. Using a normative legal method with statutory, conceptual, and historical approaches, this study identifies regulatory gaps. The findings reveal that the amendment to the State Ministry Law, particularly the revision of Article 15, which allows ministry numbers to be determined by presidential discretion, creates legal uncertainty. This fails to meet two key indicators of legal certainty theory - lex stricta and lex certa - leading to detrimental implications for ministry formation. This study recommends a judicial review of the amendments and advocates for reinstating a maximum limit on ministry numbers within the legal framework. This regulatory provision enhances legal certainty and prevents potential abuse of authority.